2020
DOI: 10.3389/fpsyg.2020.01962
|View full text |Cite
|
Sign up to set email alerts
|

Changing Body Representation Through Full Body Ownership Illusions Might Foster Motor Rehabilitation Outcome in Patients With Stroke

Abstract: How our brain represents our body through the integration of internal and external sensory information so that we can interact with our surrounding environment has become a matter of interest especially in the field of neurorehabilitation. In this regard, there is an increasing interest in the use of multisensory integration techniques-such as the use of body ownership illusions-to modulate distorted body representations after brain damage. In particular, cross-modal illusions such as mirror visual feedback th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 74 publications
1
22
0
Order By: Relevance
“…One example is a study by Matamala-Gomez and colleagues (2019) [ 70 ], who investigated how altering the visual appearance of the painful virtual arm, in terms of size (big, normal, small) and transparency (0%, 25%, 50%, 75%) modulated pain perception in two different groups of chronic arm pain patients (CRPS and peripheral nerve injury (PNI)). Interestingly, in contrast to a study conducted on healthy subjects [ 59 ], Matamala-Gomez et al (2019) [ 70 ] found that increasing the transparency of the observed virtual arm decreased pain ratings in patients with CRPS, but this did not occur in those with PNI. On the other hand, increasing the virtual arm size slightly increased pain ratings only in CRPS patients.…”
Section: Virtual Body Ownership Illusions For Mental Healthmentioning
confidence: 66%
See 4 more Smart Citations
“…One example is a study by Matamala-Gomez and colleagues (2019) [ 70 ], who investigated how altering the visual appearance of the painful virtual arm, in terms of size (big, normal, small) and transparency (0%, 25%, 50%, 75%) modulated pain perception in two different groups of chronic arm pain patients (CRPS and peripheral nerve injury (PNI)). Interestingly, in contrast to a study conducted on healthy subjects [ 59 ], Matamala-Gomez et al (2019) [ 70 ] found that increasing the transparency of the observed virtual arm decreased pain ratings in patients with CRPS, but this did not occur in those with PNI. On the other hand, increasing the virtual arm size slightly increased pain ratings only in CRPS patients.…”
Section: Virtual Body Ownership Illusions For Mental Healthmentioning
confidence: 66%
“…Today, VR is considered an advanced form of human-computer interaction that allows participants to act, communicate, and become present in an immersive computer-generated virtual environment [ 1 , 91 , 107 ]. Taking advantage of the potential of VR technology, a large number of studies have demonstrated that the sense of embodiment of a virtual body experienced during virtual BOIs can be exploited as a powerful tool for modulating some clinical disorders (e.g., motor, pain, or psychological and psychiatric disorders) by inducing changes in the patients’ internal body representation [ 59 , 61 , 70 , 108 , 109 , 110 , 111 ].…”
Section: Discussion and Future Directionsmentioning
confidence: 99%
See 3 more Smart Citations